Penguatan Literasi Ekologi melalui Pelatihan Pembuatan Batik Sastra Ekologis untuk Ibu-Ibu PKK Kelurahan Sawojajar, Kota Malang - Muhammad Aditya Wisnu Wardana; Farah Faridatul Qolbi; Siti Aisah Andani; Dita Fatimah Sari; Nourma Syafaul Fadilah; Kurnia Candra Dewi; Jihan Nada Aulia; Mohamad Irfan Fatoni; Firdaus Achmad Ghandi; Fida Pangesti (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2025)
The Ecological Literature Batik Making Project with PKK Women and the Batik Workshop Community of Sawojajar Village, Malang City is a community service activity carried out in the framework of the PPG Teacher Candidate Leadership Project Wave 2 Year 2024. This program aims to integrate the art of batik with the concept of ecological literature, as well as introduce natural dyeing methods as an environmentally friendly alternative in batik production. This activity began with an observation that found that the use of synthetic dyes in the batik industry in Malang City is still dominant, thus potentially polluting the environment. In addition, the involvement of PKK mothers in productive activities oriented towards economic sustainability and environmental conservation is still limited. The implementation of this project was conducted through a series of trainings and workshops that included an introduction to hand-drawn batik techniques as a cultural heritage, an understanding of ecological literature in batik motifs, and the practice of making natural dyes using indigofera. Participants were also trained to apply the concept of ecological literature in batik designs made in various products, such as totebags, cushions and tablecloths. The results of this activity show that the active participation of the community in batik training with natural dyes can increase awareness of more environmentally friendly textile production practices. It is hoped that this project can become a sustainable movement in the use of natural dyes in the batik community in Malang City and open up new economic opportunities for the community, especially PKK mothers. In addition, through the introduction of ecological literature in batik motifs, this activity also contributes to educating the public about the relationship between humans and the environment through textile art.